The thalamus - Halassa, Michael (Cambridge University Press, 2023)
"The organization of thalamic afferents solves a computational constrain introduced by a peculiar feature of the vertebrate forebrain systems. In all vertebrate species, studied far (including basal branches like Cyclosotomata, the lamprey), (Suryanarayana et al., 2017, 2020) the top level information processor (i.e. the cortex, or pallium) has very little direct access to fast, accurate, excitatory (i.e. glutamatergic) inputs from subcortical (subpallial) structures beside thalamus. In other words cortex has minimal precisely timed information about the rest of the brain without a thalamic transfer. Since thalamus has virtually no local axon collaterals, its inputs and the integration of these inputs will define the message the cortex will work on. Thalamic inputs can be of cortical or subcortical origin (Sherman & Guillery, 2005). Subcortical inputs to the thalamus carry information about the outside world as well as the inner state of the animals (including motor, motivational, anxiety etc. states), as a consequence, this information is extremely diverse by nature (Jones, 2007a). This results in versatile representations and complex integration of subthalamic inputs at the level of thalamus. Large fraction of these subcortical inputs are involved in cortico-subcortico-cortical loops (e.g. basal ganglia, the cerebellar loop or the Papez circuit) closed via the thalamus through pathways utilizing various transmitters and terminal types (Guillery & Sherman, 2011). Thalamic activity requires a constant and immediate update from the target region of the thalamus, the cortex"--
Keywords: Thalamus